Protein S exacerbates alcoholic hepatitis by stimulating liver natural killer T cells. (11th December 2014) - Chelakkot‐Govindalayathil, A.‐L.; Mifuji‐Moroka, R.; D'Alessandro‐Gabazza, C. N.; Toda, M.; Matsuda, Y.; Gil‐Bernabe, P.; Roeen, Z.; Yasuma, T.; Yano, Y.; Gabazza, E. C.; Iwasa, M.; Takei, Y.
Summary Background Alcohol consumption is a major cause of liver injury but the mechanisms are not completely understood. Protein S (PS) is an anticoagulant glycoprotein with multiple functions. The role of PS in liver injury is unknown. Objectives This study investigated the role of PS in acute alcoholic hepatitis. Methods A mouse overexpressing human PS (hPS‐TG) was generated in which acute hepatitis was induced by intraperitoneal injection of ethanol. Results The levels of serum liver enzymes and liver tissue inflammatory cytokines and the degree of hepatic steatosis were significantly increased in hPS‐TG mice treated with ethanol compared with ethanol‐treated wild type (WT) mice. Cell expansion, activation and inhibition of apoptosis were significantly augmented in natural killer T (NKT) cells from hPS‐TG mice compared with WT mice. Liver mononuclear cells from hPS‐TG mice express higher levels of inflammatory cytokines than those from WT mice after stimulation with a specific stimulant of NKT cells in vitro. In a co‐culture system of hepatocytes and NKT cells, the effects of PS on ethanol‐mediated cell injury were suppressed by a CD1d neutralizing antibody. Alcoholic liver injury was significantly improved in mice pre‐treated with PS siRNA and anti‐protein S antibody compared with control mice. Patients with alcoholic hepatitis showed significantly increased plasma PS levels and enhanced liver expression of PS and CD1d compared with controls. Conclusions The results of this study suggest that PS exacerbates acute alcoholic hepatitis by inhibiting apoptosis of activated NKT cells.